2006
DOI: 10.1124/mol.106.030726
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of Structure-Activity Relationships of Antitumor Platinum Complexes by Acetoxime but Not Hydroxylamine Ligands

Abstract: The presence of cis-configured exchangeable ligands has long been considered a prerequisite for antitumor activity of platinum complexes, but over the past few years, several examples violating this structure-activity relationship have been recognized. We report here on studies with the geometric isomers of [PtCl 2 (acetoxime) . We found that 2 (trans) is 16 times more cytotoxic than 1 (cis) and as cytotoxic as cisplatin in cisplatin-sensitive ovarian carcinoma cells (CH1). Moreover, 2 (trans) is 15 times mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 32 publications
1
43
0
Order By: Relevance
“…[51,[55][56][57][58][59] Interaction of 1 with the model compound 9-ethylguanine (9EtG) was investigated under different conditions. Incubation of 1 with 9EtG at molar ratios of 1:1 and 1:2 resulted in formation of the respective 9EtG adduct by exchange of a chlorido ligand (two diastereomers at approximately 139 and 141 ppm in the Mass spectrometric studies of a mixture of 1 and 9EtG (1:1) after 24 h of reaction revealed, in addition to a peak assignable to unchanged 9EtG at m/z 180.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…[51,[55][56][57][58][59] Interaction of 1 with the model compound 9-ethylguanine (9EtG) was investigated under different conditions. Incubation of 1 with 9EtG at molar ratios of 1:1 and 1:2 resulted in formation of the respective 9EtG adduct by exchange of a chlorido ligand (two diastereomers at approximately 139 and 141 ppm in the Mass spectrometric studies of a mixture of 1 and 9EtG (1:1) after 24 h of reaction revealed, in addition to a peak assignable to unchanged 9EtG at m/z 180.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…It has been applied to investigate the stability of novel compounds but also the interactions of drugs with biomolecules, such as human serum proteins [8][9][10][11][12][13][14][15] and nucleotides [16][17][18][19][20][21], elucidating possible metabolic and reaction pathways of the drug candidates [6,7,16], notably always working under simulated physiological conditions with regard to pH, temperature, aqueous solutions, and/or buffer composition.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the binding of 5 0 -dGMP toward a series of cis-and trans-Pt(II) amine (cisplatin and transplatin, acetoxime, and hydroxylamine compounds; for structural formulae see Fig. 1) was studied by CZE and the binding was compared to that of plasmid DNA and a dsDNA fragment by gel electrophoresis [56]. The formation of 5 0 -dGMP adducts of the platinum complexes could be followed by CZE with UV/Vis detection, which is quite indicative for the formation of such species.…”
Section: Other Platinum Complexesmentioning
confidence: 99%